Vitamin A derivative tablet and preparation method thereof
By using a specific proportion of microcrystalline cellulose and magnesium stearate in retinoic acid tablets, combined with the powder direct pressure process, the stability of retinoic acid tablets under high temperature and high humidity light conditions was solved, and good dissolution was achieved Performance and stability are superior to commercially available preparations.
Patent Information
- Application Number
- CN202411632880.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-15
AI Technical Summary
Under light, high temperature and high humidity conditions, the impurity and total impurity content of existing retinoic acid tablets have a large change and insufficient stability, which affects their dissolution performance and clinical application.
Using 11%-12% retinoic acid, 83%-87.8% of two microcrystalline cellulose compound and 1.0%-2.0% of magnesium stearate, the retinoic acid tablets were prepared by direct powder pressing process, and the During the preparation process, control the process parameters such as stirring and shear speed, mixing time, tablet hardness and coating weight gain to ensure the stability of the tablet.
The stability and dissolution performance of retinoic acid tablets are significantly improved. The impurity and total impurity content changes slightly under high temperature and high humidity light conditions, and the dissolution curve is close to that of commercially available preparations, extending the effectiveness of the drug.
Smart Images

Figure CN119258027A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of pharmaceutical chemistry, and specifically relates to a retinoic acid tablet and a preparation method thereof. Background Art
[0002] A vitamin A derivative tablet, retinoic acid tablet, the main ingredient of which is all-trans retinoic acid, is a cell differentiation inducing drug with a wide range of medical uses. Its chemical name is 3,7-dimethyl-9-(2,6,6-trimethylcyclohexene)-2,4,6,8-all-trans nonatetraenoic acid, and its molecular formula is C 20 H 28 O2, molecular weight is 300.44. The drug is a light yellow tablet with good oral absorption. It is mainly used to treat various skin diseases and acute promyelocytic leukemia (APL). The research and development background of retinoic acid tablets can be traced back to the in-depth study of vitamin A and its metabolites. As a metabolic intermediate of vitamin A, retinoic acid plays an important role in regulating cell growth, differentiation and metabolism. With the deepening of the understanding of the pathogenesis of APL, scientists have found that retinoic acid can induce the differentiation and maturation of APL cells, thus becoming an important drug for the treatment of APL. In addition, retinoic acid has also shown good efficacy in the treatment of various skin diseases, further broadening its clinical application range.
[0003] The existing retinoic acid tablets on the market (sold by Shandong Liangfu Pharmaceutical Co., Ltd.) have been exposed to light, high temperature, and high humidity accelerated tests. The impurity G and total impurities in the bare tablets and coated tablets have gradually increased, and both exceeded the limit in March; the growth of impurity G and total impurities in the packaged samples has improved, but the impurities are still large at 10 days and 90 days. Therefore, while ensuring the basic performance such as dissolution performance, improving the stability of retinoic acid tablets is still a problem that needs to be solved. Summary of the invention
[0004] The present application provides a tretinoin tablet having good dissolution performance and stability.
[0005] A retinoic acid tablet comprises: by weight percentage, 11%-12% retinoic acid, 83%-87.8% of a compound of two types of microcrystalline cellulose, and 1.0%-2.0% of magnesium stearate.
[0006] In a specific embodiment of the present invention, the two microcrystalline celluloses are selected from TF series, TL series.
[0007] In a specific embodiment of the present invention, the two microcrystalline celluloses are TF525 and TL565.
[0008] In a specific embodiment of the present invention, the weight ratio of the two types of microcrystalline cellulose is 32-39:39-45.
[0009] In a specific embodiment of the present invention, the weight ratio of the two types of microcrystalline cellulose is 39:40.
[0010] In a specific embodiment of the present invention, the two microcrystalline celluloses are TF525 and The weight ratio of TL565 is 39:40.
[0011] In a specific embodiment of the present invention, a tretinoin tablet comprises: by weight percentage, 11.11% tretinoin, 87.78% of a combination of two types of microcrystalline cellulose, and 1.11% magnesium stearate.
[0012] The present invention also provides a method for preparing tretinoin tablets, comprising:
[0013] 1) Weighing: weigh the raw materials and excipients according to the prescription amount and pass through a 40-mesh sieve;
[0014] 2) Total mixing: Add the materials into the wet granulator, set the stirring speed to 220-280 rpm, the shear speed to 1000-1600 rpm, and the mixing time to 5-10 min;
[0015] 3) Tableting: Theoretical tablet weight is 180±13mg, hardness is controlled at 30-50N;
[0016] 4) Coating: coating weight gain 3-5%;
[0017] 5) Aluminum bag: The heat sealing temperature is set to 110-140℃ and the main engine speed is 4-8rpm.
[0018] Beneficial effects:
[0019] 1) Excellent stability: After a large number of experiments, the inventors discovered a new formula for tretinoin tablets. Only two types of microcrystalline cellulose are compounded in a certain proportion, and a lubricant, magnesium stearate, is added. The tretinoin tablets are made through a powder direct compression process. The formula is simple and the chemical properties are stable. After accelerated experiments under high temperature, high humidity and light conditions, it can still maintain good stability. Compared with the existing tretinoin tablets on the market, the impurity G and the content of single impurities and total impurities change less.
[0020] 2) Dissolution is close to that of commercially available preparations: The inventors adjusted the new formula to prepare tretinoin tablets, which have a dissolution curve that is close to that of commercially available preparations in the same medium. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present application are clearly described below. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of the present application.
[0022] The terms "first", "second", etc. in the specification and claims of this application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than those described here, and the objects distinguished by "first", "second", etc. are generally of one type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the objects associated before and after are in an "or" relationship.
[0023] The present application is not limited to the above-mentioned specific implementation modes, which are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are protected by the present application.
[0024] The present application provides a retinoic acid tablet, comprising: by weight percentage, 11%-12% retinoic acid, 83%-87.8% of a compound of two types of microcrystalline cellulose, and 1.0%-2.0% of magnesium stearate. The weight percentage of the two types of microcrystalline cellulose can be 83%, 85%, 87.8%, preferably 87.8%.
[0025] Preferably, the microcrystalline cellulose is selected from TF series, TL series. TF series microcrystalline cellulose and TL series microcrystalline cellulose is produced by Zhuhai Dongchen Pharmaceutical Co., Ltd. TF series microcrystalline cellulose can be TF515, TF525, TF915, TF925; TL series crystalline cellulose can be TL565 and TL965.
[0026] Preferably, the two microcrystalline celluloses are TF525 and TL565.
[0027] Preferably, the weight ratio of the two microcrystalline celluloses is 32-39:39-45, and can be 32:40, 35:40, 39:40, 39:39, 39:45, and is preferably 39:40.
[0028] Preferably, two kinds of microcrystalline cellulose TF525 and The weight ratio of TL565 is 39:40.
[0029] Preferably, a tretinoin tablet comprises: by weight percentage, 11.11% tretinoin, 87.78% of a combination of two microcrystalline celluloses, and 1.11% magnesium stearate.
[0030] The present invention also provides a method for preparing tretinoin tablets, comprising:
[0031] 1) Weighing: weigh the raw materials and excipients according to the prescription amount and pass through a 40-mesh sieve;
[0032] 2) Total mixing: Add the materials into the wet granulator, set the stirring speed: 220-280rpm, the shear speed: 1000-1600rpm, and the mixing time: 5-10min; the stirring speed can be 220rpm, 240rpm, 280rpm; the shear speed can be 1000rpm, 1200rpm, 1600rpm; the mixing time is 5min, 8min, 10min;
[0033] 3) Tableting: Theoretical tablet weight is 180±13mg, hardness is controlled at 30-50N;
[0034] 4) Coating: coating weight gain 3-5%;
[0035] 5) Aluminum bag: The heat sealing temperature is set to 110-140℃, the main engine speed is 4-8rpm, the heat sealing temperature can be 110, 120, 140℃, the main engine speed is 4rpm, 6rpm, 8rpm.
[0036] The retinoic acid tablets prepared by the invention have excellent dissolution performance and stability.
[0037] Example 1
[0038] 1) 2000 20mg / tablet retinoic acid tablets. See Table 1 for the prescription quantity.
[0039] Table 1 Example 1 Prescription
[0040] Material Name 2000 large-size retinoic acid tablets prescription quantity (g) Retinoic acid 40 Microcrystalline Cellulose TF525 156 Microcrystalline Cellulose TL565 160 Magnesium Stearate 4 total 360
[0041] 2) Mixing process see Table 2
[0042] Table 2 Example 1 Mixing process
[0043]
[0044] 3) See Table 3 for large-scale tableting process parameters
[0045] Table 3 Tableting process parameters of Example 1
[0046]
[0047] 4) Coating process parameters are shown in Table 4
[0048] Table 4 Coating process parameters of Example 1
[0049]
[0050]
[0051] The formula for calculating coating weight gain is as follows:
[0052]
[0053] Coating weight gain is about: 5%
[0054] 5) Aluminum package process parameters are shown in Table 5
[0055] Table 5 Aluminum cladding process parameters of Example 1
[0056] Heat sealing temperature 130℃ Host speed 6 rpm
[0057] The difference between Examples 2 to 3 and Comparative Examples 1 to 5 and Example 1 is that the two types of microcrystalline cellulose are different. The microcrystalline cellulose used in Examples 2 and 3 is selected from TF series, TL series, comparative examples 1 to 5 are respectively configured to use only one type of microcrystalline cellulose, not all of them TF series and TL series of microcrystalline cellulose, no use TF series and In the comparative experiment of TL series of microcrystalline cellulose, other conditions including the total amount of microcrystalline cellulose used, the weight ratio of the two types of microcrystalline cellulose, the amount of other auxiliary materials used, and all process conditions were the same. Detailed data are shown in Table 6.
[0058] The difference between Examples 4 to 6 and Comparative Examples 6 to 9 and Example 1 is only that the weight ratio of the two microcrystalline celluloses is different. In Examples 4 to 6, the weight ratio of the two microcrystalline celluloses is set between 32 to 39:39 to 45, while Comparative Examples 6 to 9 respectively set experiments in which the weight ratio of the two microcrystalline celluloses is not within the above range. Other conditions including the type of microcrystalline cellulose, the total amount of microcrystalline cellulose used, the amount of other auxiliary materials used and all process conditions are the same. Detailed data are shown in Table 6.
[0059] Table 6 List of variables in Examples 1-7 and Comparative Examples 1-11
[0060]
[0061]
[0062] The stability test was performed on the retinoic acid tablets prepared in Examples 1-6 and Comparative Examples 1-9. The 20 mg / tablet retinoic acid tablets (batch number 231001) sold by Shandong Liangfu Pharmaceutical Co., Ltd. were selected as the standard preparation. An accelerated test was performed under high temperature 60°C, high humidity 95%, and light 5000Lx to examine the impurity content and active substance content in the retinoic acid tablets at 30 days, 90 days, and 180 days under the above conditions. It is known that under high temperature, high humidity, and light, the content of impurity G and each impurity in the retinoic acid tablets changes significantly, and the impurity information is shown in Table 7.
[0063] Table 7 Impurity information
[0064]
[0065]
[0066] Causes of impurities:
[0067] Impurities A to F mentioned in the above table are all included in the European Pharmacopoeia 10.0 edition, among which impurity A is also included in the Chinese Pharmacopoeia 2020 edition. Impurity A is isotretinoin, which is both a process impurity of retinoic acid and a degradation impurity. Impurities B, D and G are also process impurities and degradation impurities. Impurities C and F are process impurities that may be generated during the synthesis of raw materials. Impurities A, B, D and G are easily degraded under hot and humid conditions.
[0068] The measurement results of the impurity contents and active ingredient contents of the tretinoin tablets prepared in Examples 1-6 and Comparative Examples 1-9 and commercially available preparations under high temperature 60°C, high humidity 95%, and light 5000Lx are shown in Table 8 below.
[0069] Table 8 Measurement results of impurity contents and active ingredient contents of Examples 1-6 and Comparative Examples 1-9 under high temperature 60°C, high humidity 95%, and light 5000Lx
[0070]
[0071]
[0072]
[0073]
[0074] Note: ND means not detected
[0075] Comparing Examples 1, 2, 3 and Comparative Examples 1 to 4, it can be seen that after Examples 1, 2, and 3 were placed under high temperature, high humidity, and light conditions for 3 months and 6 months, the content of impurity G, total impurities, and active substances changed slightly; after Comparative Examples 1 to 4 were placed under the same conditions for 3 months and 6 months, the content of impurity G, total impurities, and active substances changed greatly. Therefore, when other conditions are the same, microcrystalline cellulose is selected from TF series, TL series, the retinoic acid tablets produced are more stable.
[0076] Comparing Examples 1, 4, 5, 6 and Comparative Examples 6, 7, 8, 9, it can be seen that after Examples 1, 4, 5, 6 were placed under high temperature, high humidity and light conditions for 3 months and 6 months, the content of impurity G, total impurities and active substances in Examples 1, 4, 5, 6 changed little; after Comparative Examples 6, 7, 8, 9 were placed under the same conditions for 3 months and 6 months, the content of impurity G, total impurities and active substances changed greatly. Therefore, when other conditions are the same, the two microcrystalline cellulose TF525 and When the weight ratio of TL565 is 32-39:39-45, the obtained retinoic acid tablets are more stable.
[0077] Comparing Examples 1 to 6 with commercially available preparations, it can be seen that after Examples 1 to 6 were placed under high temperature, high humidity and light conditions for 3 months and 6 months, the changes in the contents of impurity G, total impurities and active substances in Examples 1 to 6 were smaller than those in the commercial preparations under the same conditions for 3 months and 6 months. Therefore, it can be seen that the stability of the retinoic acid tablets provided by the present invention is better than that of commercially available preparations.
[0078] The dissolution performance of the tretinoin tablets prepared in Examples 1-6 and Comparative Examples 1-9 was evaluated.
[0079] Referring to the dissolution and release determination method (Chinese Pharmacopoeia 2020 Edition, Part IV, General Rules, 0931, Method 2), water, 0.1 mol / L HCl solution, pH 4.5 acetate buffer, and pH 6.8 phosphate buffer were used as dissolution media, respectively, at a speed of 100 rpm. The operation was carried out in accordance with the law, and samples were taken at 5 min, 10 min, 15 min, 20 min, 30 min, 45 min, and 60 min, respectively. The dissolution data of the retinoic acid tablets prepared in Examples 1-6 and Comparative Examples 1-9 were tested. The detailed data are shown in Table 9.
[0080] Table 9 Dissolution data of retinoic acid tablets prepared in Examples 1-6 and Comparative Examples 1-9
[0081]
[0082]
[0083]
[0084]
[0085] The f2 factors of the dissolution curves of the tretinoin tablets prepared in Examples 1-6 and Comparative Examples 1-9 and commercially available preparations were tested. The results are shown in Table 10.
[0086] Table 10 Dissolution curve f2 factor of retinoic acid tablets and reference reagents prepared in Examples 1-6 and Comparative Examples 1-9
[0087]
[0088]
[0089] Comparing Examples 1 to 3 with Comparative Examples 1 to 4, it can be seen that the dissolution factors f2 of Examples 1 to 3 and the commercially available preparations in water, 0.1 mol / L HCl solution, pH 4.5 acetate buffer, and pH 6.8 phosphate buffer as dissolution media are relatively large compared with the dissolution factors f2 of Comparative Examples 1 to 4 under the same conditions. Therefore, when other conditions are the same, the microcrystalline cellulose selected from TF series, In the TL series, the dissolution of the prepared tretinoin tablets is closer to that of the commercially available preparations.
[0090] Comparing Examples 1, 4, 5, 6 with Comparative Examples 6, 7, 8, 9, it can be seen that the dissolution factors f2 of Examples 1, 4, 5, 6 in water, 0.1 mol / L HCl solution, pH 4.5 acetate buffer, and pH 6.8 phosphate buffer as dissolution media with the commercial preparation are relatively large compared with the dissolution factors f2 of Comparative Examples 6, 7, 8, and 9 under the same conditions. Therefore, when other conditions are the same, the two microcrystalline cellulose TF525 and When the weight ratio of TL565 is 32-39:39-45, the dissolution of the prepared tretinoin tablets is closer to that of the commercially available preparations.
[0091] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present application, but the present application is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present application, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A vitamin A derivative tablet, characterized in that: include: Calculated by weight percentage, the invention comprises 11%-12% of retinoic acid, 83%-87.8% of a compound of two kinds of microcrystalline cellulose, and 1.0%-2.0% of magnesium stearate.
2. A vitamin A derivative tablet according to claim 1, characterized in that: The two microcrystalline celluloses are respectively selected from TF series, TL series.
3. The vitamin A derivative tablet according to claim 1, characterized in that: The two microcrystalline celluloses are TF525 and TL565.
4. The vitamin A derivative tablet according to claim 1, characterized in that: The weight ratio of the two microcrystalline celluloses is 32-39:39-45.
5. The vitamin A derivative tablet according to claim 1, characterized in that: The weight ratio of the two microcrystalline celluloses is 39:
40.
6. The vitamin A derivative tablet according to claim 3, characterized in that: The microcrystalline cellulose is TF525 and The weight ratio of TL565 is 32~39:39~45.
7. The vitamin A derivative tablet according to claim 3, characterized in that: The microcrystalline cellulose is TF525 and The weight ratio of TL565 is 39:
40.
8. The vitamin A derivative tablet according to claim 1, characterized in that: include: In terms of weight percentage, the proportions of the components are: 11.11% retinoic acid, 87.78% combination of two types of microcrystalline cellulose, and 1.11% magnesium stearate.
9. The method for preparing a vitamin A derivative tablet according to any one of claims 1 to 8, characterized in that: include: 1) Weighing: weigh the raw materials and excipients according to the prescription amount and pass through a 40-mesh sieve; 2) Total mixing: Add the materials into the wet granulator, set the stirring speed to 220-280 rpm, the shear speed to 1000-1600 rpm, and the mixing time to 5-10 min; 3) Tableting: Theoretical tablet weight is 180±13mg, hardness is controlled at 30-50N; 4) Coating: coating weight gain 3-5%; 5) Aluminum package: The heat sealing temperature is set to 110-140℃ and the main engine speed is 4-8rpm.
10. The method for preparing a vitamin A derivative tablet according to claim 9, characterized in that: include: 1) Weighing: weigh the raw materials and excipients according to the prescription amount and pass through a 40-mesh sieve; 2) Total mixing: Add the materials into the wet granulator, set the stirring speed to 240 rpm, the shear speed to 1200 rpm, and the mixing time to 8 min; 3) Tableting: Theoretical tablet weight is 180±13mg, hardness is controlled at 40N; 4) Coating: coating weight gain 5%; 5) Aluminum bag: The heat sealing temperature is set to 120℃ and the main engine speed is 6rpm.
Citation Information
Patent Citations
Ranolazine sustained release tablet medicine composition and preparation method thereof
CN104758265A
Isotretinoin A acid particle preparation method
CN106580888A
Tadalafil tablet and preparation method thereof
CN115089551A
Pharmaceutical tableting method
EP0196546A2
Pharmaceutical composition comprising mirabegron and process for manufacturing the same
WO2021069944A1